A revision of the genus Orosius Distant (Hemiptera: Cicadellidae) based on male genitalia and DNA barcoding. Issue 2 (1st September 2016) - Fletcher, Murray; Löcker, Holger; Mitchell, Andrew; Gopurenko, David
Abstract: A morphological and molecular review of the genus Orosius Distant (Deltocephalinae: Opsiini) was undertaken using male genitalia and DNA barcoding. We recognise 14 valid species of the genus, of which two were indeterminate, based on females only and recognised only by DNA barcodes. Orosius argentatus (Evans) stat. rev. is removed from synonymy with Orosius orientalis (Matsumura) after DNA barcoding demonstrated that the two species are distinct; small but consistent differences in the male genitalia are also found to support the two species hypothesis. The other species, recognised on male genitalia, are confirmed with DNA barcode sequence data. These species are Orosius albicinctus Distant, Orosius lotophagorum (Kirkaldy), Orosius canberrensis (Evans), Orosius ryukyuensis (Ishihara) and Orosius cellulosus (Lindberg), plus five new species described herein as Orosius albifrons Fletcher & Löcker sp. nov. and Orosius brunneus Fletcher & Löcker sp. nov. from Barrow Island, Western Australia, Orosius recurvus Fletcher & Löcker sp. nov. from New South Wales and Orosius magareyi Fletcher & Löcker sp. nov. and Orosius pallidus Fletcher & Löcker sp. nov. from Loxton, South Australia. This is the first record of O. cellulosus from Australia. Orosius aegypticus Ghauri syn. nov. is synonymised with O. albicinctus, the synonymy of Nesaloha cantonis Oman syn. nov. is transferred to O. orientalis from O. argentatus and Orosius argentatus novaebrittaniae Ghauri syn. nov. is synonymised with O. orientalis. Orosius minuicus Dlabola is excluded from the genus. A key for the discrimination and identification of the species based on male genitalia is provided.